A simple and effective isocratic HPLC method for fast identification and quantification of surfactin - Muhammad Qadri Effendy Mubarak; Mohd Hafez Mohd Isa; Hassan A.R.; Hamid A.A.; Khalil S. (Penerbit Universiti Kebangsaan Malaysia, 2024)
Indexed by WOS/ Scopus